Impact of Salt Intake and RAAS blockade on lung SARS CoV-2 Host Factors - Xiaoli Zhang; Liping Liu; Mohamed M.S. Gaballa; Ahmed A Hasan; Yingquan Xiong; Li Xie; Thomas Klein; Denis Delic; Burkhard Kleuser; Bernhard K. Krämer; Jian Li; Berthold Hocher (Karger Publishers, 2022)
Introduction: The angiotensin-converting enzyme 2 (ACE2) as well as the transmembrane protease serine type 2 (TMPRSS2) have been found to play roles in cell entry for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus causing Coronavirus disease 2019 (COVID-19). SARS-CoV-2 infection risk and severity of COVID-19 might be indicated by the expression of ACE2 and TMPRSS2 in the lung. Methods: A high salt diet rat model and RAAS blockade were used to test whether these factors affect ACE2 and TMPRSS2 expression of the lung. A normal (0.3% NaCl), a medium (2% NaCl), or a high (8% NaCl) salt diet was fed to rats for 12 weeks, along with enalapril or telmisartan, before examining the lung for histopathological alteration. Using immunofluorescence and qRT-PCR, the localization as well as mRNA expression of ACE2 and TMPRSS2 were investigated. Results: The findings provide evidence that both TMPRSS2 and ACE2 are highly expressed in bronchial epithelial cells as well as ACE2 was also expressed in alveolar type2 (AT2) cells. High salt diet exposure in rats leads to elevated ACE2 expression on protein level. Treatment with RAAS blockers had no effect on lung tissue expression of ACE2 and TMPRSS2. Conclusions: These findings offer biological support regarding the safety of these drugs that are often prescribed to COVID-19 patients with cardiovascular co-morbidity. High salt intake on the other hand might adversely affect COVID-19 outcome. Our preclinical data should stimulate clinical studies addressing this point of concern.